Healthcare professionals’ needs when providing perinatal bereavement care: A qualitative study - Giti Atashsokhan; Maryam Farjamfar; Ahmad Khosravi; Mahboobe Taher; Khadige Abadian; Afsaneh Keramat (Journal of Education and Health Promotion, 2024)
BACKGROUND: Caring for and supporting bereaved parents with fetal loss requires preparation, training, and attention to a set of needs of health workers to provide optimal services. This is although it has been less addressed in the educational curriculum and in-service training. This study aims to investigate the experiences of Iranian healthcare professionals regarding the needs related to the care of bereaved parents with perinatal loss. MATERIALS AND METHODS: This research was a qualitative study conducted in Shahroud City, Iran, to explore healthcare professionals’ needs from June 2021 to December 2022. Semi-structured in-depth interviews on purposive sample of 14 participants were conducted. The participants were care providers who worked in OB-GYN ward, general midwifery clinics, and a private office. The interviews were recorded verbatim, transcribed, and analyzed using an inductive content analysis. MAXQDA software version 10 was used for data analysis. Granheim and Lundman’s approach was used to analyze the data. RESULTS: Two major themes, four categories, and nine subcategories emerged. The themes included the “existence of protective laws and policies” and “skill and training needs.” Protective laws and policies included “Government Rules and guidelines” and “organizational Rules protecting the individual.” Skills and training needs consisted of two categories: “communication skills” and “Self-Care needs.” CONCLUSIONS: Educational policies, development of guidelines for the care of bereaved mothers based on culture, training programs for dealing with bereaved parents, providing self-care programs for employees, and improving the physical and emotional conditions of the workplace were among the needs expressed by the participants. Meeting the needs of healthcare professionals is effective in job satisfaction, feeling of value, and high quality of services for bereaved parents.